Like a Grinding Stone: How Crowdfunding Platforms Create, Perpetuate, and Value Health Inequities. (Medical Anthropology Quarterly, 2021)
This article explores how inequities are reproduced by, and valued within, the increasingly ubiquitous world of medical crowdfunding. As patients use platforms like GoFundMe to solicit donations for health care, success stories inundate social media. But most crowdfunders experience steep odds and marginal benefits. Drawing on the problematic figure of the "black box" in health disparities research and technology studies, I offer ethnography as a tool for unpacking often inscrutable and complex pathways through which online platforms amplify inequities. By leveraging both online and traditional research strategies—a platform analysis and paired narratives of crowdfunders' disparate experiences, drawn from open‐ended interviews—this article explores how inequities are created and experienced by users. The analysis highlights how inequities are simultaneously central to the functioning of this marketplace and occluded by its platform design. Consequently, crowdfunding is concealing health inequities while shifting public values about who is entitled to health care, and why.